2007
DOI: 10.1146/annurev.neuro.30.051606.094341
|View full text |Cite
|
Sign up to set email alerts
|

Ventral Tegmental Area Neurons in Learned Appetitive Behavior and Positive Reinforcement

Abstract: Ventral tegmental area (VTA) neuron firing precedes behaviors elicited by reward-predictive sensory cues and scales with the magnitude and unpredictability of received rewards. These patterns are consistent with roles in the performance of learned appetitive behaviors and in positive reinforcement, respectively. The VTA includes subpopulations of neurons with different afferent connections, neurotransmitter content, and projection targets. Because the VTA and substantia nigra pars compacta are the sole sources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
425
2
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 536 publications
(442 citation statements)
references
References 184 publications
(246 reference statements)
14
425
2
1
Order By: Relevance
“…Cellular and molecular studies of long-term potentiation (LTP) and long-term depression (LTD) of neurotransmission onto neuronal targets of dopamine add ostensible mechanisms for prediction and learning about rewards that give pleasure (Berke 2003;Fields et al 2007;Hyman et al 2006;Kelley 2004;Malenka and Bear 2004). Similarly, studies of learning consolidation, and of striatum-accumbens interactions with associative brain structures such as amygdala, hippocampus, prefrontal cortex, and anterior cingulate cortex, have been conducted in support of this hypothesis (Balleine 2005;Balleine and Killcross 2006;Cardinal and Everitt 2004;Cohen et al 2005;Everitt and Robbins 2005;Feldman Barrett and Wager 2006;Schultz 2006).…”
Section: Controversial Subcortical Pleasure Generators? Dopamine and mentioning
confidence: 99%
“…Cellular and molecular studies of long-term potentiation (LTP) and long-term depression (LTD) of neurotransmission onto neuronal targets of dopamine add ostensible mechanisms for prediction and learning about rewards that give pleasure (Berke 2003;Fields et al 2007;Hyman et al 2006;Kelley 2004;Malenka and Bear 2004). Similarly, studies of learning consolidation, and of striatum-accumbens interactions with associative brain structures such as amygdala, hippocampus, prefrontal cortex, and anterior cingulate cortex, have been conducted in support of this hypothesis (Balleine 2005;Balleine and Killcross 2006;Cardinal and Everitt 2004;Cohen et al 2005;Everitt and Robbins 2005;Feldman Barrett and Wager 2006;Schultz 2006).…”
Section: Controversial Subcortical Pleasure Generators? Dopamine and mentioning
confidence: 99%
“…Dopamine neurons are found mainly in the VTA and the neighboring substantia nigra pars compacta (SNpc) (D'Ardenne et Fields et al, 2007;Luo et al, 2011). The dopaminergic signal in the VTA reflects the valence of the feedback received (rewarding or punishing), and the degree to which the feedback was expected, referred to as "prediction error" (Bromberg-Martin et al, 2010b, 2010cSchultz, 2010).…”
Section: Role Of Dopamine In Learning and Memory Consolidationmentioning
confidence: 99%
“…How is this phasic change in firing activity translated into DA release at target structures? Experimental data has shown that a single-pulse stimulation applied to the VTA or the median forebrain bundle leads to a DA release lasting a few seconds (Kilpatrick et al 2000;Fields et al 2007;Phillips et al 2003;Robinson et al 2002;Roitman et al 2004;Yavich and MacDonald 2000). The probability of release of DA is however lower than that of glutamate and is varies greatly among DA synapses (Daniel et al 2009).…”
Section: (T)mentioning
confidence: 99%